Insects as feed: species selection and their potential use in Brazilian poultry production. Issue 4 (1st December 2017) - Allegretti, G.; Schmidt, V.; Talamini, E.
Abstract : The growing global demand for soybeans due to its different uses and by-products, as well as its use in the diet of several livestock species, is forcing the industry to seek alternative protein sources. Environmental concerns related to huge volumes of poultry manure serve as a warning for the choice of more sustainable production systems. Thus, the current review investigates the processing of an insect meal as an alternative protein source to feed broilers. The five desirable features in the selection of insect species proposed by the Food and Agriculture Organization (FAO) show that the high productivity of biomass, feed conversion efficiency and the organic waste conversion capacity from poultry farms is aided by the use of larvae from housefly and black soldier fly species. Brazilian production of such insects is possible due to climatic and environmental conditions and has the potential to supply part of the protein demands of the Brazilian poultry industry when raised in controlled environments. The prevalence of tropical climatic conditions and the possible use of organic waste from poultry farms as substrate can mitigate some environmental issues as well as generate income to smallholder farms prevailing in this activity.